A new phenylpropane-pimarane heterodimer and a new ent-kaurene diterpene from the husks of Oryza sativa. (April 2018) - Zhang, Qiang; Xu, Qiao-Lin; Xia, Xiao-Mei; Dong, Li-Mei; Luo, Bi; Liu, Wen-Bin; Tan, Jian-Wen
Graphical abstract: Highlights: New diterpene derivatives1 and2 were isolated from the husks of Oryza sativa . Ent -kaurene diterpenoid3 was obtained as a plant natural product for the first time. Compounds1 and3 showed inhibitory activity against two rice pathogenic fungal strains. Abstract: A new phenylpropane-pimarane heterodimer, 2-[( E )-3-(4-hydroxy-3-methoxyphenyl) allylidene] momilactone A (1 ), and a new ent -kaurene diterpene, ent -3α, 16α-dihydroxy-kauran-19-oic acid (2 ), were isolated from the rice husks of Oryza sative L., along with a known ent -kaurene diterpenoid ent -7-oxo-kaur-15-en-19-oic acid (3 ). Their structures were determined by spectroscopic means, including nuclear magnetic resonance (NMR) and mass spectrometry (MS) techniques. Compound3 was isolated as a natural product for the first time. These compounds were tested for their in vitro antifungal activity against rice pathogenic fungi Magnaporthe grisea and Rhizoctonia solani . Compounds1 and3 were found to show anti-fungal activity against M. grisea and R. solani with MIC values ranging from 6.25 to 25 μg/mL. No inhibitory activity was detected for compound2 in this bioassay.